Clinical Genetics of Polydactyly: An Updated Review - Umair, Muhammad; Ahmad, Farooq; Bilal, Muhammad; Ahmad, Wasim; Alfadhel, Majid (Frontiers in Genetics, 2018)
Polydactyly, also known as hyperdactyly or hexadactyly is the most common hereditary limb anomaly characterized by extra fingers or toes, with various associated morphologic phenotypes as part of a syndrome (syndromic polydactyly) or may occur as a separate event (non-syndromic polydactyly). Broadly, the non-syndromic polydactyly has been classified into three types i.e; preaxial polydactyly (radial), central polydactyly (axial) and postaxial polydactyly (ulnar). Mostly inherited as an autosomal dominant entity with variable penetrance and caused by defects that occur in the anterior-posterior patterning of limb development. In human, to-date at least ten loci and six genes causing non-syndromic polydactyly have been identified, including the ZNF141, GLI3, MIPOL1, IQCE, PITX1, and the GLI1. In the present review, clinical, genetic and molecular characterization of the polydactyly types has been presented including the recent genes and loci identified for non-syndromic polydactyly. This review provides an overview of the complex genetic mechanism underlie polydactyly and might help in genetic counseling and quick molecular diagnosis.